KUALITAS AUDIT DALAM PERSPEKTIF SKEPTISME PROFESIONAL DAN PENGALAMAN AUDITOR YANG DIMODERASI OLEH TIME BUDGET PRESSURE - Nindya Rizqita Aulina, - (2021)
This study aims to determine the effect of professional skepticism and auditor experience on audit quality moderated by time budget pressure on auditors in DKI Jakarta. The sampling method used is convenience sampling with a total of 65 auditors from 16 accounting firms in DKI Jakarta. This study use primary data with a questionnaire technique google form link. Hypothesis testing is done by using version 3.0 SmartPLS software. The result of hypothesis testing show that professional skepticism, auditor experience and time budget pressure have a significant positive effect on audit quality, and time budget pressure as a moderating variable moderates the relationship between professional skepticism on audit quality while time budget pressure does not moderate auditor experience on audit quality. The result of this study imply that professional skepticism, auditor experience and time budget pressure have an important role in improving the quality of audits produced by auditors so that auditors can produce better audit quality even though in this study time budget pressure could not moderate the relationship of professional skepticism to audit quality and auditor's experience on audit quality.